The Modeling Toolkit: how recruitment strategies for modeling positions influence model progress - Melsen, Lieke A. (Frontiers in Water, 2023)
Hydrological models play a key role in contemporary hydrological scientific research, but the social practices surrounding the use of these models receive little attention. This study focuses on the recruitment process for scientific positions in which models are used, to understand the implications for model development. Over 400 scientific hydrological vacancies were analyzed, to evaluate whether the job description already prescribed which model must be used, and whether experience with a specific model was an asset. Of the analyzed job positions, 76% involved at least some modeling. Of the PhD positions that involved any modeling, the model is already prescribed in the vacancy text in 17% of the cases, for postdoc positions this was 30%. A small questionnaire revealed that also beyond the vacancies where the model is already prescribed, in many Early-Career Scientist (ECSs) projects the model to be used is pre-determined and, actually, also often used without further discussion. There are valid reasons to pre-determine the model in these projects, but at the same time, this can have long-term consequences for the ECS. An ECS develops a “Modeling Toolkit”, a toolkit that contains all the models where the ECS has experience with. This toolkit influences the research identity the ECS develops, and influences future opportunities of the ECS—it might be strategic to gain experience with popular, broadly used models, or to become part of an efficient modeling team. This serves an instrumental vision on modeling and maintains the status quo. Seeing models as hypotheses calls for a more critical evaluation. ECSs learn the current rules of the game, but should at the same time actively be stimulated to critically question these rules.